2009
DOI: 10.1080/00016350902976779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a chemomechanical method for caries removal in children and adolescents

Abstract: The chemomechanical caries removal technique is an adequate alternative to the conventional rotary instruments method and is advantageous in pediatric dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 29 publications
2
18
0
8
Order By: Relevance
“…This was comparable with the treatment time found in the present study. In another study done by Maragakis et al (2001) in which the time required for caries removal by air-motor was 11.8 ± 3.4 s and that by Carisolv was 411 ± 157.2 s. Other studies by Nadanovsky et al (2001), Fure et al (2000), Bergmann et al (2005), Lozano-Chourio et al (2006 and Peric et al (2009) also found the Carisolv method to be more time consuming than drilling.…”
Section: Time Taken For Removal Of Cariesmentioning
confidence: 81%
See 1 more Smart Citation
“…This was comparable with the treatment time found in the present study. In another study done by Maragakis et al (2001) in which the time required for caries removal by air-motor was 11.8 ± 3.4 s and that by Carisolv was 411 ± 157.2 s. Other studies by Nadanovsky et al (2001), Fure et al (2000), Bergmann et al (2005), Lozano-Chourio et al (2006 and Peric et al (2009) also found the Carisolv method to be more time consuming than drilling.…”
Section: Time Taken For Removal Of Cariesmentioning
confidence: 81%
“…Similar results have been observed in the study of Ericson et al (1999) where the completeness of caries removal was judged by the use of a sharp explorer, air-rotor had shown the greatest efficacy in removal of caries. Other studies by Fure et al (2000), Bergmann et al (2005), Lozano-Chourio et al (2006) and Peric et al (2009) and compared the efficacy of caries removal by airrotor and Carisolv by the use of explorer and concluded that Carisolv was an equally effective method for caries removal as the air-rotor method.…”
Section: Efficacy Of Caries Removalmentioning
confidence: 95%
“…From the selected studies, two were conducted in India [9,21], one in Venezuela [18], two in Greece [10,22], one in Lithuania [16], one in Serbia [15], one in Sweden [14], one in the US [23] and one in both Denmark and Portugal [17]. Two of the papers reported data from multi-center (Sweden; Denmark and Portugal) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Few in vivo studies evaluate Carisolv Ò efficacy: the results seem to support the reliability of the chemo mechanical caries removal [9,10,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…10,17,18,21 The patient satisfaction rates of Carisolv use ranged between 70% to 90%, 25,71-73 and also showed marked reduction for the need for local anaesthesia. 74 However, some studies have reported negative feedback with regard to the unpleasant taste and odour of Carisolv. 27,49,75 Several studies have evaluated the pain response and patient satisfaction rate after Papacarie treatment.…”
Section: Clinical Aspects Of Chemomechanical Caries Removalmentioning
confidence: 99%